Crop rotation and sequence effects on temporal variation of CO2 emissions after long-term no-till application - Xavier, Clariana Valadares [UNESP]; Moitinho, Mara Regina; Teixeira, Daniel De Bortoli; de Araújo Santos, Gustavo André [UNESP]; Corá, José Eduardo [UNESP]; La Scala, Newton [UNESP] (Elsevier, 2020)
Production, transport, and emission of CO2 from soil to the atmosphere are directly influenced by soil temperature and moisture conditions, exhibiting a high variability over time due to the influence of climate events and soil management practices. Thus, this study aimed to investigate the effect of summer and off-season crop residues on the temporal variation of soil CO2 emission (FCO2), soil temperature (Tsoil), and soil moisture (Msoil) under a no-till system that has been managed with the same crop arrangement for >16 years. The experiment was conducted in strips with three replications. Treatments consisted of summer crop sequences maize monoculture, soybean monoculture, and soybean-maize rotation, as well as off-season crops maize, millet, pigeon pea, grain sorghum, and crotalaria. Sixteen assessments of FCO2, Tsoil, and Msoil were carried out over 51 days. A significant effect of the interaction between time and summer crop sequences (F = 1.44; p = 0.02) and between time and off-season crops (F = 2.26; p < 0.01) was observed for FCO2. Moreover, a triple interaction was observed between summer crop sequences, off-season crops, and time for Msoil (F = 1.83; p < 0.01) and Tsoil (F = 1.32; p = 0.01). The values of FCO2 and Msoil were high on days 229 and 230 due to precipitations in the study area. The relationship between FCO2 and Msoil was positive in all the assessed management, and about 60% of FCO2 variation over the study period could be explained by soil water content variation.
Keywords: Cover crop; Crop residues; Crop sequence; Soil moisture; Soil respiration